The origins of pottery in East Asia - Kuzmin, Yaroslav V. (Documenta Praehistorica, 2015)
Recent developments related to the emergence of pottery in East Asia and neighbouring regions are presented. According to a critical evaluation of the existing evidence, the oldest centres with pottery in East Asia are situated in South China (dated to c. 18 000 calBP), the Japanese Islands (c. 16 700 calBP), and the Russian Far East (c. 15 900 calBP). It is most likely that pottery-making appeared in these regions independently of each other. In Siberia, the earliest pottery now known is from the Transbaikal region (dated to c. 14 000 calBP). However, it did not influence the more west- erly parts of Siberia in terms of the origin and spread of pottery-making.
Keywords: arheološke najdbe; ceramic; datiranje; Japonska; keramika; Kitajska; lončarstvo; prazgodovina; Rusija; Sibirija